The Effectiveness of the Msme Internal Control System is Broken Down Into: Purpose, Commitment, Capability, and Monitoring & Learning - Nikmatuniayah; Marliyati; Siti Mutmainah; Jati Handayani; Lilis Mardiana Anugrahwati (Sinergi International Journal of Accounting and Taxation, 2026)
This study aims to identify the Internal Control System (ISC) based on COCO and Business Continuity in Micro, Small, and Medium Enterprises (MSMEs). The population of this study was creative industry MSMEs in Semarang City. A purposive sampling technique was used to select 120 samples, each with an age of more than one year. This study used a Google form distributed to selected creative industry owners. This study employed qualitative and quantitative methods with a descriptive approach to internal control based on COCO. Data were processed through descriptive statistical tests and SPSS. This study can identify purpose, commitment, capability, and Monitoring and Learning as having a significant and indirect influence on Accounting through Going Concern. Going Concern functions as a significant mediating variable in the relationship between Purpose, Commitment, Capability, and Monitoring and Learning on Accounting. This research empirically proves that internal control systems support the sustainability of MSME businesses. Accounting practices also significantly influence MSME business continuity.